Depression, subjective cognitive decline, and the risk of neurocognitive disorders - Liew, Tau Ming (Alzheimers Res Ther, 2019)
BACKGROUND: Depression and subjective cognitive decline (SCD) both predict neurocognitive disorders (NCD). However, the two correlate strongly with each other. It remains uncertain whether they reflect independent neurobiological underpinnings which deserve separate attention. This study evaluated the independent risks of NCD associated with depression and SCD. METHODS: This cohort study included 13,462 participants who were ≥ 50 years and had normal cognition at baseline. The participants were evaluated for depression and SCD and followed up almost annually for incident mild cognitive impairment or dementia (MCI/dementia) (median follow-up = 4.4 years). Depression and SCD were included in Cox-regression to investigate their independent risks of MCI/dementia. RESULTS: At baseline, 1307 participants (9.7%) had depression and 3582 (26.6%) had SCD. During follow-up, 1490 (11.1%) developed MCI/dementia. Depression and SCD demonstrated independent risks of MCI/dementia (HR 1.4 and 2.0 respectively). The risk was highest when depression and SCD co-occur (HR 2.8), with half of the participants in this group developing MCI/dementia within 7.2 years of follow-up (compared to 12.2 years in participants without depression or SCD). CONCLUSIONS: The findings may change the clinical approach in managing SCD in depression, suggesting the need for greater emphasis on detecting prodromal NCD. They may also have implications to our understanding of NCD, suggesting the need for further research to delineate the commonalities and distinctions in the neurobiological pathways of depression and SCD. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13195-019-0527-7) contains supplementary material, which is available to authorized users.